EXPERIMENTAL AND NUMERICAL INVESTIGATION OF FLEXIBLE BURIED PIPE DEFORMATION BEHAVIOR UNDER VARIOUS BACKFILL CONDITIONS - Terzi, Niyazi Ugur; Yildirim, Sonmez (PAMUKKALE UNIV, 2009)
Deformation characteristics of polyethylene based flexible pipes are different than rigid pipes such as concrete and iron pipes. Deflection patterns and stress-strain behaviors of flexible pipes have strict relation between the engineering properties of backfill and its settlement method. In this study, deformation behavior of a 100 mm HDPE flexible pipe under vertical loads is investigated in laboratory conditions. Steel test box, pressurized membrane, raining system, linear position transducers and strain gauge rosettes are used in the laboratory tests. In order to analyze the buried pipe performance; Masada Derivation Formula which is mostly used by designers is employed. According to the test and mathematical studies, it is understood that relative density of backfill and its settlement method is a considerable effect on buried pipe performance and Masada Derivation method is very efficient for predicting the pipe performance.
Keywords: HDPE buried flexible pipe; Laboratory test; Masada derivation formula; Engineering